2011
DOI: 10.1186/1471-2458-11-351
|View full text |Cite
|
Sign up to set email alerts
|

A hepatitis A, B, C and HIV prevalence and risk factor study in ever injecting and non-injecting drug users in Luxembourg associated with HAV and HBV immunisations

Abstract: BackgroundIn Luxembourg, viral hepatitis and HIV infection data in problem drug users (PDUs) are primarily based on self-reporting. Our study aimed to determine the prevalence of HAV, HBV, HCV and HIV infections in ever injecting (IDUs) and non-injecting drug users (nIDUs) including inherent risk factors analysis for IDUs. Secondary objectives were immunisation against HAV and HBV, referral to care and treatment facilities as well as reduction in risk behaviour.MethodsA nationwide, cross-sectional multi-site s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 19 publications
2
29
1
Order By: Relevance
“…The association between older age and the increased risk for HCV infection was consistent with those of earlier studies [Removille et al, 2011;Hope et al, 2012]. Since older age also regarded as a cofactor that accelerates the progression of liver disease [Shepard et al, 2005], older injecting drug users would be regarded as the risk group in which early detection of HCV is important.…”
Section: Discussionsupporting
confidence: 73%
“…The association between older age and the increased risk for HCV infection was consistent with those of earlier studies [Removille et al, 2011;Hope et al, 2012]. Since older age also regarded as a cofactor that accelerates the progression of liver disease [Shepard et al, 2005], older injecting drug users would be regarded as the risk group in which early detection of HCV is important.…”
Section: Discussionsupporting
confidence: 73%
“…drug users was estimated to be 53% in [2001][2002][2003]. For the same period, HBsAg prevalence was 6.0%-8.4% in this risk group Brack [17] Retrospective cohort study (n=1791) Removille et al [18] Cross-sectional study, Luxembourg…”
Section: Study Setting Resultsmentioning
confidence: 99%
“…F Indication group 2: Persons at increased risk of non-occupational exposure.Examples: Persons living together with HBsAg carriers [11,12,13], persons at high risk of acquiring hepatitis B by sexual contact [11,14,15], people who inject drugs [14,16,17], prison inmates [18,19,20], psychiatric inpatients [21,22]. F Indication group 3: Persons at increased risk of occupational exposure.Examples: Health care personnel (HCP) at risk of exposure (including trainees, laboratory personnel, cleaning personnel) [23,24,25], first aiders [26,27], police officers [29], personnel of facilities where an increased prevalence of HBV-infected persons is likely to be present (e.g., correctional facilities, asylum seeker shelters, homes for the handicapped) [18,19,20,27,28,29].…”
Section: Schlüsselwörtermentioning
confidence: 99%
“…Studies have shown elevated prevalence of HIV infection among NIDU worldwide, ranging from 3.7% in México to 16.0% in the United States of America (11)(12)(13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%